2005
DOI: 10.1002/ajmg.b.30249
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary comparison of the hopes of researchers, clinicians, and families for the future ethical use of genetic findings on schizophrenia

Abstract: A written questionnaire about genetic testing was distributed to all registrants at The 2004 World Congress of Psychiatric Genetics, mailed to clinical psychiatrists obtained from a directory of clinicians practicing in New York City, and mailed to members of families who have multiple affected family members with schizophrenia. A total of 274 individuals responded (162 researchers, 64 clinicians, and 48 family members). This survey shows that the majority of family members who completed the questionnaire (83.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
107
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 16 publications
13
107
0
Order By: Relevance
“…12,15,22,23,29 The results suggest having a personal or family experience of depression, bipolar disorder or schizophrenia may be a strong predictor of uptake of predictive genetic testing for mental disorders. As the National estimated lifetime risk for mental illness is estimated to be 20-25%, it is expected that a proportion of a population sample would report personal or family experience of depression or other mental disorders.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…12,15,22,23,29 The results suggest having a personal or family experience of depression, bipolar disorder or schizophrenia may be a strong predictor of uptake of predictive genetic testing for mental disorders. As the National estimated lifetime risk for mental illness is estimated to be 20-25%, it is expected that a proportion of a population sample would report personal or family experience of depression or other mental disorders.…”
Section: Discussionmentioning
confidence: 95%
“…Similar concerns were described in a study of attitudes towards predictive genetic testing for susceptibility to schizophrenia. 22 The majority of participants who were interested in having the hypothetical test said they would still have it despite the result offering a probabilistic rather than a definitive risk. These findings support a previous study on families with a high density of bipolar disorder, which revealed a comparably higher degree of perceived disadvantages of a probabilistic risk versus certainty of risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychiatrists recognize the need to incorporate genetics into psychiatric practice (Finn et al, 2005;Hoop et al, 2008), but many lack expertise and/or confidence in this area (Finn et al, 2005;Abbate et al, 2014). Given growing evidence indicating that people with psychiatric disorders and their families would like to receive genetic counseling (DeLisi and Bertisch, 2006;Lyus, 2007;Austin and Honer, 2008;Peay et al, 2009), psychiatry is an area of practice that potentially presents an ideal scenario for fruitful interdisciplinary collaboration between physicians and genetic counselors (Thompson et al 2015). Indeed, clear benefits have been demonstrated for individuals who have received genetic counseling for psychiatric illnesses, including improved understanding of causes of mental illness, reduced concern about other relatives becoming affected, and feeling more hopeful, in control, better able to cope and help, and reduced anxiety, self-blame and guilt (Austin and Honer, 2008;Costain et al, 2012Costain et al, , 2014Inglis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that individuals with psychotic illnesses and their families are interested in knowing about the chances for other family members to be affected (DeLisi and Bertisch, 2006;Lyus, 2007). Further, in the absence of consultation about risks for children to be affected with psychotic illnesses, unaffected relatives of individuals with psychosis make their own estimations of what probabilities for children to be affected might be.…”
Section: Introductionmentioning
confidence: 99%